Etika Digital Dan Penyebaran Hoaks - Sinaga, Arnold Ropen; Alamsyah, Nur; Hermawan, Arief Karditya (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
The development of digital technology has driven significant transformation in the agribusiness sector, creating new opportunities while also presenting challenges. The background of this study stems from the urgent need to enhance the efficiency and competitiveness of the agricultural sector through the utilization of digital technology. The aim of this research is to identify the challenges and explore the opportunities in implementing digital agribusiness in Indonesia. A descriptive qualitative approach was employed, with data collected through literature review and interviews with agribusiness practitioners and technology experts. The findings indicate that digitalization opens up opportunities in terms of market access, increased productivity, and distribution efficiency. However, challenges such as limited infrastructure, low digital literacy among farmers, and unequal access to technology remain major obstacles. In conclusion, to optimize the potential of digital agribusiness, a collaborative strategy involving the government, private sector, and educational institutions is needed to create an inclusive and sustainable ecosystem.